Assessment of Adult Individuals' Fear of COVID-19, Healthy Living Behaviors, and Nutrition Knowledge Levels during the COVID-19 Pandemic Period - Saltekin, Ayşe; Erzurum Alim, Nural (Jurnal Gizi dan Pangan, 2024)
This study determines the fear of COVID-19, healthy lifestyle behaviors, and nutrition knowledge levels of individuals during the COVID-19 pandemic. The study was conducted involving 509 people between the ages of 18 and 64 from December 2020 to April 2021. Data were collected online using a descriptive characteristics form, the COVID-19 Fear Scale, the Adult Nutrition Knowledge Level Scale, and the Healthy Lifestyle Behaviors Scale II. It was found from the study that women feared COVID-19 more than men (p<0.05). Individuals aged 35–44 scored higher in basic nutrition knowledge, while those aged 18‒24 scored lower in food preference knowledge (p<0.05). It was also found that individuals who were between 55 and 64 years of age, married, highly educated, employed in the public sector, of good economic status, and ill scored higher on the Healthy Lifestyle Behaviors Scale II (p<0.05). A weak positive correlation was found between the score of the Fear of COVID-19 Scale and scores of both food preference knowledge and health responsibility sub-dimensions (r=0.088, r=0.181; p<0.05). A weak positive correlation was also found between the nutrition knowledge score as well as the different sub-dimensions and the total score of the Healthy Lifestyle Behaviors Scale II (r=0.164, r=0.196; p<0.05). It was observed that fear of COVID-19, nutrition knowledge level, and healthy lifestyle behaviors were influenced by various socio-demographic characteristics, and that there was a relationship between these three elements.